Let "x" represent the shorter leg of the triangle.
Then, the long leg is 7m longer than the shorter leg, we can represent this as "x+7"
And the hypothenuse is 9m longer than the shorter leg, we can represent this as "x+9"
The Pythagoras theorem states that the square of the hypothenuse is equal to the sum of the squares of the sides of the triangle, so that:
![a^2+b^2=c^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/fdnnfwrccw5g60jmi691r5gcz9ekxf8waa.png)
a: shortest leg
b: longest leg
c: hypothenuse
Replace with the expressions for each side:
![x^2+(x+7)^2=(x+9)^2](https://img.qammunity.org/2023/formulas/mathematics/college/g0rq1jmhmyj79lm289i34mp58bb4idpbpb.png)
First solve both square of the binomials separatelly from the main expression:
1)
![\begin{gathered} (x+7)^2=(x+7)(x+7) \\ x^2+7x+7x+49 \\ x^2+14x+49 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wudw9e03nltdjxqp15dw48s2277znf2u6y.png)
2)
![\begin{gathered} (x+9)^2=(x+9)(x+9) \\ x^2+9x+9x+81 \\ x^2+18x+81 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e3x8hvf5llrhuoy1232i9a17itsjfrg0ir.png)
Now that both terms are solved, input the results in the main expression
![\begin{gathered} x^2+(x+7)^2+(x+9)^2 \\ x^2+(x^2+14x+49)=(x^2+18x+81) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ecob909pqj0jss3mhrebp7hvkksg9bntcb.png)
Now we need to equal the expression to zero, so perform the inverse operation to pass all terms to the left side of the equal sign
![\begin{gathered} x^2+(x^2+14x+49)-x^2-18x-81=x^2-x^2+18x-18x+81-81 \\ x^2+x^2+14x+49-x^2-18x-81=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nc50mrbkk88y1cfqj0a60tu1xt3xgajnnw.png)
Order all like terms together and simplify:
![\begin{gathered} x^2+x^2-x^2+14x-18x+49-81=0 \\ x^2-4x-32=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xbpmyl9y7934u0b0sv844xi4sa0ip18rba.png)
With this, we stablished a quadratic expression. Using the quadratic formula we have to calculate the possible values of x
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
For our expression
a=1
b=-4
c=-32
Imput these values in the formula and calculate:
![\begin{gathered} x=\frac{-(-4)\pm\sqrt[]{(-4)^2-4\cdot1\cdot(-4)}}{2\cdot1} \\ x=\frac{4\pm\sqrt[]{16+16}}{2} \\ x=\frac{4\pm\sqrt[]{32}}{2} \\ x=\frac{4\pm4\sqrt[]{2}}{2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ok6b3vlg7u0n8wetu00vpo364shq158j0h.png)
Now calculate both values of x:
Positive
![\begin{gathered} x=\frac{4+4\sqrt[]{2}}{2} \\ x=2+2\sqrt[]{2} \\ x\cong4.828 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/su0eox6zo3yxzlsp90yot7wvc0e1toq9oa.png)
Negative
![\begin{gathered} x=\frac{4-4\sqrt[]{2}}{2} \\ x=2-2\sqrt[]{2} \\ x\cong-0.828 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kf67rw0j75bdmnba9g43vc22gx797rr8db.png)
The length of the side of a triangle cannot be a negative value, so the only possible value of x will be:
![x=2+2\sqrt[]{2}=4.828m](https://img.qammunity.org/2023/formulas/mathematics/college/d63ujyogg4b3mkotc3u88plz583kuo6ugz.png)
Now that we know the value of the shortest leg, we can calculate the value of the longest leg and the hypothenuse:
Longest leg
![x+7=(2+2\sqrt[]{2})+7=9+2\sqrt[]{2}\cong11.828m](https://img.qammunity.org/2023/formulas/mathematics/college/64k73miegf82sxopmmpu44nbgoo8s22165.png)
Hypothenuse
![x+9=(2+2\sqrt[]{2})+9=11+2\sqrt[]{2}\cong13.828m](https://img.qammunity.org/2023/formulas/mathematics/college/ozo0sl2vy8a9wp5rwxv1u1xsvodbht6co5.png)